Peningkatan Fisik Motorik Menggunakan Modifikasi Permainan Pada Pembelajaran Penjas Melalui Lesson Study Di SDIB KBRI Thailand - Bahrul Ulum; Frendy Aru Fantiro; Bustanol Arifin (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
This research aims to improve children's physical motor skills through physical education learning at Indonesian Elementary Schools at the Indonesian Embassy in Thailand in the form of game modifications. Game modification in sports learning needs to be done to create new innovations in the field of sports education, which is no less important than fulfilling the growth and development of elementary school children. It aims to accommodate the needs at every stage of concrete operational development experienced by elementary school children abroad, it is necessary to use concrete games for children and develop children's physical motor skills. This study employed a qualitative descriptive method that focused on improving physical motor skills using game modifications in physical education through a Lesson Study. The design that has been carried out using the Pre-Experimental Design type of research in the form of Lesson Study Implementation at the SDIB Indonesian Embassy in Thailand can be the Key to the Implementation of Research using Lesson Study in SDIB of the Indonesian Embassy in Thailand that at the planning stage that has been prepared for RPP, LK and evaluation of LS learning, the stages are carried out by model teachers accompanied by observers and the research team., LS is carried out in 2 cycles each. The data on the results of increasing the physical motor skills of 4th-grade students of the Indonesian Embassy in Thailand in the first cycle was 72.5; Cycle II is 77, which means that the modification of the game has an impact on students' physical motor skills as well as on the enthusiasm and activeness of students in carrying out learning activities and so that the results of students' motoric physical ability from cycle I to cycle II have increased.